The twentysomething treatment : a revolutionary remedy for an uncertain age - Jay, Meg (Simon & Schuster, 2024)
"There is a young adult mental health crisis in America. So many twentysomethings are struggling-especially with anxiety, depression, and substance use-yet, as a culture, we are not sure what to think or do about it. Perhaps, it is said, young adults are snowflakes who melt when life turns up the heat. Or maybe, some argue, they're triggered for no reason at all. Yet, even as we trivialize twentysomething struggles, we are quick to pathologize them and to hand out diagnoses and medications. Medication is sometimes, but not always, the best medicine. For twenty-five years, Meg Jay has worked as a clinical psychologist who specializes in twentysomethings, and here she argues that most don't have disorders that must be treated: they have problems that can be solved. In these pages, she offers a revolutionary remedy that upends the medicalization of twentysomething life and advocates instead for skills over pills"--